Spatiotemporal air quality variation between urban and agricultural areas: the influence of climatic factors and pollution dynamics - ZAINAB N. ABDULATEEF; ADEL H. TALIB; MAITHAM A. SULTAN (Journal of Agrometeorology)
Air pollution is a critical environmental and meteorological concern, significantly influenced by climatic conditions and atmospheric dynamics. Hence, the present study examines seasonal and daily variations in the concentrations of air pollutants, such as CO, SO₂, NOₓ, and O₃, in Baghdad, based on the principle of meteorological influences during the wet and dry seasons. Data were collected at 23 transportation intersections in addition to an agricultural area during morning and afternoon periods. The results indicated a robust relationship between the levels of pollutants and meteorological conditions. Carbon monoxide showed an afternoon peak during the dry season owing to air stagnation (28.2–18.7 ppm). Ozone concentrations also heightened in this season due to increased temperature and photochemical reactions (0.515–0.35 ppm). Levels of ozone, sulfur dioxide and nitrogen oxides reflect over-national air quality standards, with maxima seen in the dry season and more so in the afternoons. The results of the Air Quality Index analysis show that the main factors causing a drastic decrease in quality during the dry season are higher temperatures, scanty rainfall, and increased levels of photochemical activity. This result emphasizes the need to integrate meteorology into urban planning to mitigate pollution.